Optical Coherence Tomography in the Diagnosis and Monitoring of Retinal Diseases. (26th February 2013) - Ţălu, Simona-Delia
Abstract : Optical coherence tomography (OCT) allows the visualization of the retinal microarchitecture as cross-sectional or tomographic volumetric data. The usefulness of OCT in the management of various retinal diseases is validated by the possibility to allow early diagnosis and to help in the decision-making process. OCT is applied by two main methods: time domain (TD-OCT) and spectral domain (SD-OCT). The advantages of SD-OCT over TD-OCT are significant improvement of the image axial resolution, decreased acquisition times, reduction of motion artifacts, increased area of retinal sampling, and the possibility to create topographic maps by the three-dimensional evaluation of tissues. OCT is the most precise method to measure the central macular thickness (which is the most important practical parameter) in vivo. It has been demonstrated that there are differences in the retinal thickness measurements between OCT models, explained by the higher axial and transverse resolutions of the newer devices. Further research has led to significant improvements in OCT technology represented by ultrahigh resolution OCT (UHR-OCT), swept source OCT (SS-OCT), enhanced depth imaging OCT (EDI-OCT), and adaptive optics. Technological progress in OCT imaging offered new perspectives for better understanding the retinal diseases, opening new avenues for the fundamental and clinical research. This is a review of the data in the literature concerning the evolution of OCT technology in the field of retinal imaging.